2010
DOI: 10.2514/1.43868
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Asteroid Fragmentation During Impact Hazard Mitigation

Abstract: The consequences of the fragmentation of an Earth threatening asteroid due to an attempted deflection are examined in this paper. The minimum required energy for a successful impulsive deflection of a threatening object is computed and compared to the energy required to break-up a small size asteroid. The results show that the fragmentation of an asteroid that underwent an impulsive deflection, such as a kinetic impact or a nuclear explosion, is a very plausible event. A statistical model is used to approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Some studies also discuss the fragmentation which occurs upon a too large impulse being imparted, or by natural impacts. 13 15 . They show that too large impulses should be avoided for a kinetic impact.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also discuss the fragmentation which occurs upon a too large impulse being imparted, or by natural impacts. 13 15 . They show that too large impulses should be avoided for a kinetic impact.…”
Section: Introductionmentioning
confidence: 99%
“…The second best was solar sublimation with all the other methods order of magnitude less effective (according to the proposed comparison criteria). Although nuclear explosions were the most effective, a subsequent study by Sanchez et al (2010) demonstrated that for both nuclear explosions and kinetic impacts, a resulting fragmentation of the asteroid could potentially increase the risk of impact(s) on the Earth.…”
mentioning
confidence: 99%
“…This type of characterization of the fragment size distribution is presented by Sanchez, Vasile and Radice [27]. They present an accumulative power law distribution to model fragment size distribution.…”
Section: Largest Remaining Chunkmentioning
confidence: 99%
“…Past studies on side effects of disruption have focused on Earth-impact events of ejected fragments [27]. Studies by Kaplinger, Wie, and Dearborn have shown that in some cases, Earth-impacting mass can be reduced by up to 90% through a combination of nuclear disruption and atmospheric burnup [21].…”
Section: Trade Studiesmentioning
confidence: 99%
See 1 more Smart Citation